Comparison of MRI and motor evoked potential with triple stimulation technique for the detection of brachial plexus abnormalities in multifocal motor neuropathy. Issue 3 (20th December 2019) - Corazza, Giovanni; Le Corroller, Thomas; Grapperon, Aude‐Marie; Salort‐Campana, Emmanuelle; Verschueren, Annie; Attarian, Shahram; Delmont, Emilien
Abstract: Background: Conduction blocks (CB) are the diagnostic hallmark of multifocal motor neuropathy (MMN). Conventional nerve conduction studies cannot detect CB above Erb's point. Our purpose was to compare the performance of the motor evoked potential with triple stimulation technique (MEP‐TST) and MRI in the detection of abnormalities of the brachial plexus. Methods: Examinations were performed on 26 patients with MMN (11 definite, 6 probable, 9 possible), of whom 7 had no CB. Results: MEP‐TST detected proximal CB in 19/26 patients. Plexus MRI showed T2 hyperintensity in 18/26 patients, with nerve enlargement in 14/18. A combination of both techniques increased the detection rate of brachial plexus abnormalities to 96% of patients (25/26). Conclusions: MEP‐TST and MRI have high sensitivities for detecting brachial plexus abnormalities. A combination of the two techniques increases the detection rate of supportive criteria for the diagnosis of MMN.